The remaining unknowns: a mixed methods study of the current and global health research priorities for COVID-19 - Norton, A; De La Horra Gozalo, A; Feune de Colombi, N; Alobo, M; Mutheu Asego, J; Al-Rawni, Z; Antonio, E; Parker, J; Mwangi, W; Adhiambo Wesonga, C; Marsh, K; Tufet, M; et al. (BMJ Publishing Group, 2020)
INTRODUCTION: In March 2020, the WHO released a Global Research Roadmap in an effort to coordinate and accelerate the global research response to combat COVID-19 based on deliberations of 400 experts across the world. Three months on, the disease and our understanding have both evolved significantly. As we now tackle a pandemic in very different contexts and with increased knowledge, we sought to build on the work of the WHO to gain a more current and global perspective on these initial priorities. METHODS: We undertook a mixed methods study seeking the views of the global research community to (1) assess which of the early WHO roadmap priorities are still most pressing; (2) understand whether they are still valid in different settings, regions or countries; and (3) identify any new emerging priorities. RESULTS: Thematic analysis of the significant body of combined data shows the WHO roadmap is globally relevant; however, new important priorities have emerged, in particular, pertinent to low and lower middle-income countries (less resourced countries), where health systems are under significant competing pressures. We also found a shift from prioritising vaccine and therapeutic development towards a focus on assessing the effectiveness, risks, benefits and trust in the variety of public health interventions and measures. Our findings also provide insight into temporal nature of these research priorities, highlighting the urgency of research that can only be undertaken within the period of virus transmission, as well as other important research questions but which can be answered outside the transmission period. Both types of studies are key to help combat this pandemic but also importantly to ensure we are better prepared for the future. CONCLUSION: We hope these findings will help guide decision-making across the broad research system including the multilateral partners, research funders, public health practitioners, clinicians and civil society.